A Case Study of the international transfer of organisational culture between the UK based company Boden and its American Subsidiary - Shooter, Adam (2012)
This study utilises a qualitative case study framework in order to assess and compare the organisational cultures within a UK-based MNC. The company JP Boden & Co Ltd (referred to as “Boden”) is a catalogue and online clothing retailer, which, after operating in the UK for 11 years, has begun expanding internationally. After opening a returns warehouse in the United States in 2002, Boden has begun to increase its functions and employ large numbers of American nationals into the developing subsidiary. Semi-structured interviews were conducted with a total of 8 Boden employees (three American and five British) in order to identify and assess the organisational culture present in the headquarters and developing subsidiary. Additional data in the form of internal culture audits and external exit interview summaries were also analysed in order to increase the depth of understanding. The interviews focussed on employees work experiences before and during their time with Boden. The study finds that despite best efforts to duplicate the organisational culture (by Boden and the new employees) in the subsidiary, there are significant differences between the organisational cultures of the Boden headquarters and subsidiary. In particular the low Power-Distance, flattened hierarchy and core values of equality do not appear to have translated correctly to the new employees. A number of potential incompatibilities between the host country culture and Boden culture are hypothesised and discussed in light of the interview data. It appears that the lack of verbal and visual interaction with the home country employees may have lead to misunderstandings in the true values that drive the Boden culture. It is suggested that an increased presence of home country employees and more cultural training might result in a more similar organisational culture in the subsidiary.